Social presence and customer brand engagement on Facebook brand pages. Issue 3 (15th May 2017) - Pongpaew, Wimmala; Speece, Mark; Tiangsoongnern, Leela
Abstract : Purpose: Business use of social media is increasing rapidly as marketers aim to increase customer brand engagement (CBE) in brand communities to enhance the brand experience. However, use of social media for marketing communications is not well understood. This study aims to examine manager and user views of CBE and effects of perceived social presence (PSP) on CBE in a corporate Facebook environment. Design/methodology/approach: Qualitative in-depth interviews are conducted with 18 users of corporate Facebook – i.e. those who visit corporate Facebook regularly – and four marketing managers whose companies operate Facebook pages. The industry is smart-information technology devices, and the cultural context is Thailand. Findings: Corporate Facebook sites with high SP functions foster customer engagement on cognitive, emotional and behavioral levels. PSP enhances product knowledge and encourages return page visits. Thus, CBE and PSP build brand trust and loyalty. However, managers may need to focus more on the nature of the brand community beyond the corporate Facebook page. Practical implications: Companies that enrich their corporate Facebook with SP features can encourage CBE. Consumers feel more informed about the brand and therefore feel more positively about it, which enhances the brand experience and brand trust. This holds even for lurkers who do not behaviorally engage on the Facebook page much, but who are active in the broader brand community. Originality/value: This paper studies the relationship between PSP and CBE in a corporate Facebook environment, providing insights into how PSP influences CBE, which can enhance the customer's brand experience and contribute to brand perceptions.